2016
DOI: 10.1111/boj.12453
|View full text |Cite
|
Sign up to set email alerts
|

Geographical range and host breadth ofSebacinaorchid mycorrhizal fungi associating withCaladeniain south-western Australia

Abstract: Specialized mycorrhizal interactions have the potential to limit the geographical range of plant species and contribute to reproductive isolation. We investigated these predictions in Caladenia (Orchidaceae) from south‐western Australia, a group known to have specialized mycorrhizal associations with the genus Sebacina s.l. Sequencing of fungal isolates from 47 of the 136 species of Western Australian Caladenia was undertaken to resolve the geographical range and habitat preferences of mycorrhizal fungal opera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 58 publications
1
10
0
Order By: Relevance
“…Furthermore, the closely related O. provincialis, with which O. patens share the dominant symbiont [13], exhibits a larger distribution than the latter orchid species, also at a local scale (Portofino Park). Similar results were revealed in studies on the Australian genus Caladenia, where high specificity in mycorrhizal associations with sebacinoid fungi was found both in widespread and narrowly distributed orchid species, and the geographical range of the latter was far less extensive than for the OM fungi [10,63]. These observations suggest that the presence of the symbiotic fungus in the environment is not a limiting factor for the distribution of the host plant, that might be influenced by other biotic or abiotic factors.…”
Section: Distribution Of Tulasnella Helicospora In Soilsupporting
confidence: 84%
“…Furthermore, the closely related O. provincialis, with which O. patens share the dominant symbiont [13], exhibits a larger distribution than the latter orchid species, also at a local scale (Portofino Park). Similar results were revealed in studies on the Australian genus Caladenia, where high specificity in mycorrhizal associations with sebacinoid fungi was found both in widespread and narrowly distributed orchid species, and the geographical range of the latter was far less extensive than for the OM fungi [10,63]. These observations suggest that the presence of the symbiotic fungus in the environment is not a limiting factor for the distribution of the host plant, that might be influenced by other biotic or abiotic factors.…”
Section: Distribution Of Tulasnella Helicospora In Soilsupporting
confidence: 84%
“…The OM specificity may be affected by environmental factors, climate changes, extreme host selections, evolutionary history, accompanying plant species, biocompatibility, biogeographic range, and density of OMF in the soil or, for epiphytes, Frontiers in Plant Science | www.frontiersin.org phorophytes (Jacquemyn et al, 2011b(Jacquemyn et al, , 2017aMcCormick et al, 2012McCormick et al, , 2018Pandey et al, 2013;Waud et al, 2016a;Shefferson et al, 2019;Xing et al, 2019), thus showing strong and complex variations. For example, Neottia and Caladenia prefer symbiosis with sebacinales fungi (Těšitelová et al, 2015;Phillips et al, 2016;Reiter et al, 2020); the rare terrestrial orchid Caladenia huegelii specifically associates with Serendipita (= Sebacina) vermifera (Swarts et al, 2010); Cypripedium, Ophrys, and Chiloglottis prefer Tulasnellaceae (Shefferson et al, 2005(Shefferson et al, , 2019Roche et al, 2010;Schatz et al, 2010); Dendrobium nobile and Liparis japonica have high specificity for Tulasnellaceae (Ding et al, 2014;Xing et al, 2017); Pterostylis nutans and Sarcochilus weinthalii are only symbiotic with Ceratobasidium fungi (Irwin et al, 2007;Graham and Dearnaley, 2012); Platanthera leucophaea tends to be associated with Ceratobasidium fungi over a 10-year period (Thixton et al, 2020); Corallorhiza trifida shows high specificity for Thelephoraceae in different countries and varied habitats (McKendrick et al, 2000;Zimmer et al, 2008). Jacquemyn et al (2010) asserted the possibility of promoting widespread associations between orchids and available OMF in an environment devoid of water and nutrients.…”
Section: Orchid Mycorrhizal Fungal Specificitymentioning
confidence: 99%
“…Only a small difference in mycorrhizal partners was found earlier in closely related species of the genus Orchis in sympatry (Jacquemyn et al, 2011), and sexually deceptive orchids of the genus Chiloglottis were shown to share a narrow taxonomic group of Tulasnella fungi (Roche et al, 2010). Furthermore, a recent study in the sexually deceptive orchid Caladenia was also showing a strong overlap in mycorrhizal partners suggesting little contribution to reproductive isolation (Phillips, Barrett, Dalziell, Dixon, & Swarts, 2016). The consequence of the sharing of mycorrhizal fungi makes specificity of mycorrhizal symbiosis unlikely to contribute to reproductive isolation, or to enhance pre-zygotic barriers.…”
Section: Discussionmentioning
confidence: 84%